Authority of The Business Competition Supervisory Commission (KPPU) Medan Regional Office in Completing Prohibited Activities - Harahap, Nurasiah (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
The authority of the Business Competition Supervisory Commission (KPPU) Medan Regional Office I in resolving prohibited activities is crucial to regulating and ensuring the fairness of business competition in Indonesia. This research aims to dig deeper into the authority of the KPPU in handling violations that harm business competition in the region. The research method used is a literature study, which collects data from various primary and secondary sources related to KPPU regulations and practices. The research results show that the KPPU Regional Office in Medan has broad authority in detecting, investigating, and taking action against violations that violate business competition law in its region. However, challenges such as limited resources and coordination with related agencies hinder enforcing compliance. Therefore, there is a need for more integrated and synergistic efforts between the KPPU and related parties to ensure the effectiveness of business competition law enforcement and encourage healthy economic development in the region.